Menavigasi Tantangan dan Krisis: Masa Kini dan Masa Depan Pendidikan Islam pada Abad 21 - Zaidatul Inayah; Amalia, Rizka; Kurniawan, Wakib (Al-Bustan: Jurnal Pendidikan Islam, 2024)
Islamic education faces great challenges in integrating religious values with modern science in the midst of rapid social and technological change. amid rapid social and technological changes. This research aims to formulate an Islamic education paradigm that is relevant and able to overcome the problems between science and religion. and religion. The research methods used include philosophical and empirical analysis of the current Islamic education system and the application of the principles of Islamic education. empirical analysis of the current Islamic education system and the application of the principles of integrative education.principles of integrative education. The results show that Islamic education needs to adopt a theocentric and anthropocentric approach and remove the boundaries between science and religion. between science and religion. The implications of this research are the importance of curriculum renewal and teaching methods that are more holistic and adaptive to the changing times to improve the quality of education and adaptive to changing times to improve the quality of education and form individuals who are faithful, pious, and forming individuals who have faith, piety, and noble character.